2017
DOI: 10.3892/mco.2017.1259
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral contraceptive use as a risk factor and triple-negative breast cancer: A systematic review and meta-analysis

Abstract: Abstract. Triple-negative breast cancer (TNBC), a unique subtype of breast cancer, which is resistant to endocrine and targeted therapy, usually relapses early, progresses rapidly and is associated with a poor prognosis. Epidemiological investigations focusing on the association between risk factors and the onset of TNBC demonstrated that the incidence of TNBC exhibits a significant correlation with anthropometric, geographical and demographic parameters. The aim of the present systematic review and meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
1
22
1
1
Order By: Relevance
“…resulting in shorter survival (Wang et al, 2015;Li et al, 2017) TNBC diagnosis was made possible by the negative expression of hormone receptors and human epidermal growth factor receptor 2 (HER2) neu, which was reported to account for 10-20% of all BC cases (Denkert et al, 2017) TNBC is categorized by the absence of three main biomarkers, i.e. estrogen and progesterone receptors, low expression of HER2 by immunohistochemistry (IHC), and lack of amplification by fluorescence in situ hybridization (FISH) test.…”
Section: The Effects Of Low Her2/neu Expression On the Clinicopatholomentioning
confidence: 99%
See 1 more Smart Citation
“…resulting in shorter survival (Wang et al, 2015;Li et al, 2017) TNBC diagnosis was made possible by the negative expression of hormone receptors and human epidermal growth factor receptor 2 (HER2) neu, which was reported to account for 10-20% of all BC cases (Denkert et al, 2017) TNBC is categorized by the absence of three main biomarkers, i.e. estrogen and progesterone receptors, low expression of HER2 by immunohistochemistry (IHC), and lack of amplification by fluorescence in situ hybridization (FISH) test.…”
Section: The Effects Of Low Her2/neu Expression On the Clinicopatholomentioning
confidence: 99%
“…The absence of these features means that the hormonal agents and anti-HER2 treatment methods cannot be successful in treating TNBC (Kim et al, 2018;Collignon et al, 2016). The epidermal growth factor receptor (EGFR) activation stimulates cell proliferation and provide protection against apoptosis by activating protein kinase pathways (Li et al, 2017;Kim et al, 2017) Several methods, such as IHC, chromogenic in situ hybridization (CISH) and FISH are now available to quantify HER2/neu expression. (Goud et al, 2012) Hence, the aim of this study was to compare three groups of TNBCs, namely complete negative HER2 expression by IHC, minimal HER2 (1+) expression, and moderate HER2 (2+) expression by IHC and the negative FISH test for HER2 amplification.…”
Section: The Effects Of Low Her2/neu Expression On the Clinicopatholomentioning
confidence: 99%
“…Few studies have evaluated the relationship between OC use and risk of molecular subtypes of breast cancer. Some of these found that OC use is associated with increased risks of TN [3,[5][6][7] [3,6,9], ER- [4], luminal A [8,10], luminal B [8,10], TN [8,10], and H2E [3,6,8,10] breast cancers. However, three did not restrict analyses to premenopausal women [5,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…First, our study used a case-case study design, as did two others [11,12], where luminal A cases served as our reference outcome. While this study design is a limitation of the present study, as it prevented comparison with cancer-free controls as many other studies have done [3][4][5][6][7][8][9][10]22,23], it allowed us to examine the heterogeneity in the established association between OC use and breast cancer risk, by molecular subtype. We also restricted analyses to younger, premenopausal women, while others did not [5,8,9,11,12] which may explain inconsistencies with previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation